Tenofovir-induced renal tubular dysfunction among human immunodeficiency virus patients on antiretroviral therapy in Nigeria: Prospects for early detection of presymptomatic nephrotoxicity - Irikefe Paul Obiebi; Ebube Amalachukwu Nwannadi (The Korean Society of Nephrology, 2018)
Background: Tenofovir disoproxil fumarate (TDF) is relatively safe, although renal toxicity has been reported. In Nigeria, there is insufficient data on renal toxicity among patients on TDF. This study assesses TDF-associated tubular dysfunction among human immunodeficiency virus (HIV) patients at a hospital in Nigeria. Methods: In this cohort study, 104 adult HIV patients were recruited with a simple random technique from the outpatient clinic. Biochemical indices of renal function were estimated from serum and urine at the 16th and 24th week after an initial assessment at baseline. Results: There were no significant differences in baseline proteinuria or glycosuria between TDF and non-TDF groups. Mean baseline urine and serum parameters did not differ significantly between the two groups (P⟩ 0.05). In the TDF group, all urine parameters differed significantly between baseline and 24th week values (P⟨ 0.001). After 16 weeks, mean urine phosphate and urine uric acid increased significantly (P⟨ 0.05) by 2.97 mg/dL and 50.9 mg/dL, respectively, in the TDF group. The rise in mean urine glucose from baseline to the 24th week was more marked in the TDF than the non-TDF group (0.25 vs. 0.07 mmol/L). Higher mean differences in urine albumin were also recorded in the TDF group from baseline to the 24th week. Conclusion: Indicators of tubular dysfunction were markedly higher among patients on the TDF-based treatment regimen. Biomarkers of tubular dysfunction could be useful for detecting pre-symptomatic nephrotoxicity before marked reduction of glomerular filtration rate in HIV patients on TDF.